2015 IEEE Trustcom/BigDataSE/Ispa 2015
DOI: 10.1109/trustcom.2015.416
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Fake Source Algorithm for Source Location Privacy in Wireless Sensor Networks

Abstract: Original citation:Bradbury, Matthew S., Leeke, Matthew and Jhumka, Arshad (2015) A dynamic fake source algorithm for source location privacy in wireless sensor networks. Copies of full items can be used for personal research or study, educational, or not-for profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way.Publisher's statemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Similarly, Figures 2(b), 2(c) and 2(f) show that the capture ratio is either 100% or close to it for all networks with two sources, implying that the addition of a further source has done little to hinder the attacker in their pursuit of a source capture. The variation in network traffic caused by multiple sources can produce a push-pull effect on that attacker, similar to that observed in [22], that results in less informed decision making. This effect can be seen in Figure 2(c), where the attacker occasionally fails to make a capture in a two source network, leading to a capture ratio of less than 100%.…”
Section: A Protectionless Privacymentioning
confidence: 82%
See 3 more Smart Citations
“…Similarly, Figures 2(b), 2(c) and 2(f) show that the capture ratio is either 100% or close to it for all networks with two sources, implying that the addition of a further source has done little to hinder the attacker in their pursuit of a source capture. The variation in network traffic caused by multiple sources can produce a push-pull effect on that attacker, similar to that observed in [22], that results in less informed decision making. This effect can be seen in Figure 2(c), where the attacker occasionally fails to make a capture in a two source network, leading to a capture ratio of less than 100%.…”
Section: A Protectionless Privacymentioning
confidence: 82%
“…We assume that the attacker has the capability to detect the direction of message arrival and and a large amount of memory to keep track of information such as messages that have been heard. This is commensurate with the attacker models used in [5], [21], [22]. Our aim in providing SLP is to make using the context of messages too expensive for attackers, such that they instead choose to perform alternate attacks such as a brute force search of the network.…”
Section: B Attacker Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Another core principle is utilising fake sources, whereby they send padded and encrypted messages that are indistinguishable from those sent by the real source to lure the attacker in the wrong direction. Initially discounted due to suspected poor performance [4], it has since been shown that utilising fake sources can be a viable alternative to phantom routing [10,11,12]. Other works have also combined both principles into single protocols [13,14].…”
Section: Related Workmentioning
confidence: 99%